2016
DOI: 10.1007/s10147-016-0996-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of the amino acids cystine and theanine attenuates the adverse events of S-1 adjuvant chemotherapy in gastrointestinal cancer patients

Abstract: BackgroundNutritional therapy is used to reduce the adverse events (AEs) of anticancer drugs. Here, we determined whether the amino acids cystine and theanine, which provide substrates for glutathione, attenuated the AEs of S-1 adjuvant chemotherapy.MethodsPatients scheduled to receive S-1 adjuvant chemotherapy were randomized to the C/T or the control groups. The C/T group received 700 mg cystine and 280 mg theanine orally 1 week before the administration of S-1, which then continued for 5 weeks. Each group r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
2
18
3
Order By: Relevance
“…Previous research has shown that oral administration of cystine/theanine attenuates the AEs of S-1 adjuvant chemotherapy in patients with colorectal cancer after surgery. 11 The incidence rate of diarrhoea was significantly less in the cystine/theanine group (4.5%) than in the control group (41.7%). The completion rate of the first course of S-1 adjuvant chemotherapy at the prescribed dose was significantly higher in the cystine/theanine group (90.9%) than in the control group (41.7%).…”
Section: Introductionmentioning
confidence: 81%
“…Previous research has shown that oral administration of cystine/theanine attenuates the AEs of S-1 adjuvant chemotherapy in patients with colorectal cancer after surgery. 11 The incidence rate of diarrhoea was significantly less in the cystine/theanine group (4.5%) than in the control group (41.7%). The completion rate of the first course of S-1 adjuvant chemotherapy at the prescribed dose was significantly higher in the cystine/theanine group (90.9%) than in the control group (41.7%).…”
Section: Introductionmentioning
confidence: 81%
“…Sample size calculations were made based on a previous study [10]. The incidence rate of diarrhea induced by adjuvant S-1 therapy in colorectal cancer patients after surgery was significantly less in the cystine/theanine group (4.5%) than in the control group (41.7%).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this study has several limitations. First, the sample size calculation was based on a previous study on the effects of cystine/theanine on S-1-induced diarrhea [10], because we had no data of the effects of cystine/ theanine on capecitabine-induced AEs. Therefore, although capecitabine is an oral pyrimidine fluoride anticancer drug similar to S-1, and the incidence rate of diarrhea after capecitabine monotherapy is also close to that after S-1 monotherapy, our results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of cystine and theanine during the perioperative period reportedly lowered postoperative plasma interleukin‐6 levels, C‐reactive protein levels, PMN counts and body temperature in cancer patients undergoing distal gastrectomy. Moreover, this combination has been demonstrated to attenuate adverse events of S‐1 adjuvant chemotherapy in GI cancer patients . A possible mechanism might involve enhancement of glutathione metabolism by cystine and theanine …”
Section: Possible Effects Of Individual Immunonutrients On Host Responsementioning
confidence: 99%